Gelatinization properties of sago and wheat flour mixtures - Sarker, Md. Zaidul Islam; A., Abd Karim; D. M. A., Manan; Nik Ab Rahman, Nik Norulaini; A. K. M., Omar (Universiti Putra Malaysia Press, 2003)
Gelatinization or pasting properties of sago-wheat flour mixtures (10-50% sago) were studied for mixtures of sago-high protein wheat flour (HPW), sago-medium protein wheat tlour (MPW) and sago-low protein wheat flour (LPW). Gelatinization temperature (TG)increased as the sago portion in HPW, MPW and LPW increased. The peak temperature (Tp) and peak viscosity (Vp) increased with increasing sago in the sago-wheat mixtures. The setback values (5B) in sago-LPW mixtures were higher than in sago-HPW and sago-MPW mixtures. The setback viscosities (Vs) were not much different for any mixtures or control flours. The breakdown viscosities (VB) increased with increased sago in the mixtures. The breakdown value (BD) increased with increased sago in the sago-wheat mixtures.